Physical-Chemical Characterization of Soil in Two Mezcal Production Areas, in the District of Miahuatlán, Oaxaca (TERRA LATINOAMERICANA, 2025)
For the establishment of any crop, it is essential to know the properties of the soil since a lack of knowledge of the quality of the soil and its deficiencies in organic reserves and mineral nutrients becomes a limiting factor to obtain the desired yield and quality in the crop. In the present work, the physical-chemical characterization of the soil with maguey production in the municipalities of Sitio Xitlapehua and San Luis Amatlán, Miahuatlán de Porfirio Díaz, Oaxaca, was carried out to produce mezcal  under  an  artisanal  process. The  results  of the physical-chemical parameters were: pH (7.3 - 7.5), organic matter (0.26% - 3.86%), total nitrogen (0.063% - 0.463%), electrical conductivity (0.25-0.40 dS m-1), exchange capacity cationic (17.05-41.93 cmol(+) kg-1), calcium (15.67 cmol(+) kg-1 - 48.90 cmol(+) kg-1) and magnesium (1.43 cmol(+) kg-1 - 11.21 cmol(+) kg-1) exchangeable, available phosphorus (0.3 mg kg-1 - 8.0 mg kg-1) calcium carbonate (1.4% - 32.2%), bulk density (1.0 g cm-3 - 1.88 g cm-3), texture (loam, clay loam and sandy clay loam) and color (light gray, gray, black and red). Spearman correlation analysis allowed to determine the relationship between the physical-chemical variables, and the principal components analysis to identify the variables that characterize each plot. The comparison of the analyzed parameters with the NOM-021-SEMARNAT-2000 standard showed that the soils have a neutral pH, with low content of organic matter, nitrogen and phosphorus, but with high content of calcium, magnesium, calcium carbonate and capacity cation exchange. These parameters allowed us to identify the limiting factors in the nutrition of wild maguey. Based on this information, nutrition strategies will be proposed that lead to increasing the accumulation of sugars in the mature maguey and, consequently, increasing the yield in the production of mezcal.
Keywords: soil analysis; wild maguey; maguey nutrition